Methodology to Estimate the Financial Market Condition - KOSEVICH, Alexander Valentinovich; MATYUNINA, Olga Evgenievna; ZHAKEVICH, Alexander Georgievich; ZAVALKO, Natalia Aleksandrovna; LEBEDEV, Kostyantyn Anatol'evich (Journal of Advanced Research in Law and Economics, 2017)
The article systematizes theoretical approaches to the definition of product in the financial market. The system of monitoring market processes associated with shaping demand for financial assets was proposed to implement in order to monitor current trends that form the demand on the financial market and to timely detect structural imbalances. The results of the studies have shown the presence of critical foreign exchange imbalances in shaping demand on the financial market, which is due to the excessive level of its foreign currency predominance and is a testament to both the insufficient level of confidence in the national currency and the predominance of speculative motivations at the conclusion of the agreements. The formalization of the relationship between the demand for financial assets and the level of economic growth of the country has allowed to substantiate the need for the transformation of the conceptual bases of its regulation in the transition away from the traditional approach to structural regulation.